A religious space as a place for migrants in Cairo - MacDowall, Alexsa (AUC Knowledge Fountain, 2020)
The focus of this study is an international, English speaking Anglican congregation that worships in Cairo, Egypt. Through participant observation and in-depth interviews, fifteen congregants of varying nationalities and backgrounds were interviewed in order to understand how the church is a place of meaning for them, as migrants. By this congregation being the focus of study, this thesis contributes to migration research by being a non-ethnic pathway of study, religion, and it contributes to research conducted in the Global South. Findings and observations are understood primarily through the theoretical framework of space and place provided by Yi-Fu Tuan. Place making is analyzed through the lens of time, aesthetics, and people. The length of time one interacts in a space, and the intensity of their experiences in the space, contribute to knowing a space and it being endowed with meaning. Aesthetics, what they teach and reveal, the actions they call individuals to, and how they facilitate an interaction in a transcendent space additionally contribute to a space being meaningful. Lastly, through relations and social dynamics, value can be added and taken away from a space being meaningful. Findings show how meaning is not derived from one specific source, but that meaning is multi-layered and how each person attributes meaning to the church varies and differs individually, although there is overlap. This thesis aims to contribute to literature on migration, placemaking, and religion.